2009
DOI: 10.1016/j.mambio.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial HVI sequence variation in Anatolian hares (Lepus europaeus Pallas, 1778)

Abstract: Variability and phylogenetic relationships of sequences of the hypervariable domain I (HVI) of the mitochondrial DNA was studied in 46 brown hares (Lepus europaeus) from Anatolia, to test the hypotheses that (i) hares from several islands off the Anatolian coast and from Cyprus are phylogenetically close to mainland Anatolian hares, (ii) Anatolian hare sequence variability is higher than that of typical European brown hares, and to iii) infer possible Anatolian source populations of hares from some islands in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
(75 reference statements)
3
7
0
Order By: Relevance
“…As mentioned by Harris and Steudel (1997), morphological differences might be determined by ecological adaptations to different environments. Our results support the findings of Suchentrunk et al (2000), who suggested that the Sert et al (2009) reported that Anatolia's topography, with its many mountain ranges, has no significant impact on gene exchange between hare populations, and Southeast Anatolian hares with yellowish pelages are phylogenetically closely related to all other studied Anatolian hares (with brownish pelages). They also recorded that because of a lack of samples from Central and North Anatolia, the phylogenetic relationships of Anatolian hares have not been completely explained.…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned by Harris and Steudel (1997), morphological differences might be determined by ecological adaptations to different environments. Our results support the findings of Suchentrunk et al (2000), who suggested that the Sert et al (2009) reported that Anatolia's topography, with its many mountain ranges, has no significant impact on gene exchange between hare populations, and Southeast Anatolian hares with yellowish pelages are phylogenetically closely related to all other studied Anatolian hares (with brownish pelages). They also recorded that because of a lack of samples from Central and North Anatolia, the phylogenetic relationships of Anatolian hares have not been completely explained.…”
Section: Discussionsupporting
confidence: 91%
“…In that context, the aim, however, was not primarily to address overall evolutionary relationships, as using exclusively mitochondrial markers would not be appropriate, given introgression and selection in mtDNA; rather, our focus was on revealing phylogenetic relationships to classify the relative ancestral or derived status of each protein for the co-evolution analysis. The obtained results by both mitochondrial loci are by and large congruent with existing molecular and morphological data for phylogenetic inference for most of the hare taxa studied here: L. europaeus (Kasapidis et al, 2005;Sert, Ben Slimen, Erdogan, & Suchentrunk, 2009;Stamatis et al, 2009;Suchentrunk, Alkon, Willing, & Yom-Tov, 2000;Suchentrunk, Mamuris, Sfougaris, & Stamatis, 2003), L. corsicanus, L. castroviejoi, L. timidus, L. granatensis (Alves et al, 2003Alves & Hacklander, 2008;Melo-Ferreira et al, 2005), and L. habessinicus (Tolesa et al, 2017). The results of the three Mexican hare species analyzed here are also concordant with earlier findings (Cervantes, Lorenzo, & Yates, 2002) that suggested a close relationship between L. flavigularis, L. callotis, and L. californicus based on analysis of 31 allozyme loci.…”
Section: Phylogenetic Inferencessupporting
confidence: 87%
“…victoriae may also be present in Ethiopia, but as to our information no confirmed records are available. Similarly, we based species identification of all other individuals of which we currently produced sequences (Table 1) on their external phenotypes, skull and dental characters, range information (e.g., Petter[46,59], Robinson[62], Robinson and Dippenaar[51], Angermann[1], Flux and Angermann[5], Hoffmann and Smith[12], Alves and Hackländer[13], Collins[50], earlier molecular data (Sert et al[63,64], Ben Slimen et al[38, 52, 21, 31,37], Kryger[55], Kasapidis et al[14], Stamatis et al[65, 15], Suchentrunk et al[6], Suchentrunk et al[40,41]), as well as on the provisional Lepus taxonomy [5, 12, 13, 49]. …”
Section: Methodsmentioning
confidence: 99%